Recovery of an injured medial lemniscus with concurrent recovery of pusher syndrome in a stroke patient: a case report. Issue 22 (June 2018) - Jang, Sung Ho; Lee, Han Do
Abstract: Rationale: A 67-year-old, right-handed male patient underwent craniotomy and drainage for hematoma removal related to an intracerebral hemorrhage (ICH) in the right thalamus and basal ganglia at the neurosurgery department of a university hospital. Patient concerns: He presented with severe motor weakness of left extremities, impairment of proprioception, and severe pusher syndrome at the start of rehabilitation. Diagnoses: He was diagnosed as ICH in the right thalamus and basal ganglia. Interventions: The patient received comprehensive rehabilitative therapy, movement therapy, and somatosensory stimulation. Outcomes: Four months after onset, left leg motor function (Motricity Index [MI] = 51) did not show significant recovery from that at two months after onset (MI = 41); however, in the same period, Nottingham Sensory Assessment and scale for contraversive pushing significantly improved. At four months, the patient was able to stand independently but required manual contact of one person during independent walking on an even floor. At seven months after onset, he was able to walk independently on an even floor. Lessons: Recovery of a severely injured medial lemniscus with concurrent recovery of impaired proprioception and pusher syndrome.